A meta-analysis of the efficacy of allopurinol in reducing the incidence of myocardial infarction following coronary artery bypass grafting - Tejas P. Singh; Tristan Skalina; Daniel Nour; Aarya Murali; Sean Morrison; Joseph V. Moxon; Jonathan Golledge (BMC Cardiovascular Disorders, 2018)
Abstract Background The xanthine oxidase inhibitor allopurinol that is commonly used to treat gout, has been suggested to have pleiotropic effects that are likely to reduce the incidence of myocardial infarction (MI) in at risk individuals. The aim of this meta-analysis was to assess the efficacy of allopurinol treatment in reducing the incidence of MI. Method MEDLINE, Scopus, Web of Science, and Cochrane Library databases were searched for randomised controlled trials examining the efficacy of allopurinol in reducing the incidence of MI. The quality of study methodology was assessed by two independent reviewers using the Cochrane Collaboration’s tool for assessing risk of bias. This meta-analysis was conducted using a fixed-effects model, and heterogeneity was assessed with the I2 index. Results One thousand one hundred twenty-three citations were screened and only six studies satisfied the inclusion criterion. Published between 1988 and 1995, all studies examined the cardioprotective efficacy of allopurinol in the setting of coronary artery bypass graft (CABG). From a total pooled sample size of 229, MI was reported in 2 (1.77%) allopurinol and 14 (12.07%) control patients. A fixed-effects meta-analysis (I2 = 0%) identified a statistically significant reduced incidence of myocardial infarction (RR 0.21, 95% CI: 0.06, 0.70, p = 0.01) in patients allocated to allopurinol. However, in the leave-one-out sensitivity analyses, the treatment effect became non-significant with the removal of one of the studies. Conclusion Based on the limited evidence available, allopurinol appears to reduce the incidence of perioperative MI following CABG. Further research is required to confirm these findings.